Retrospective insights: clinical characteristics and survival in 403 ILC cases from China - Javaria Nasir; Boyue Han; Xin Hu; Hong Ling (BMC Cancer)
Abstract Background The objective of this study was to compare the demographic characteristics, clinicopathological factors, and survival outcomes between Invasive Lobular Carcinoma (ILC) and Invasive Ductal Carcinoma (IDC) using the Fudan University Shanghai Cancer Center (FUSCC) database. Methods Over 12,000 patients were treated at FUSCC from January 2000 to December 2019. We identified 403 patients diagnosed with ILC and 11,829 with IDC. The chi-square test was employed to compare clinical demographics, tumor characteristics, and treatments, while Kaplan–Meier survival analysis was used to obtain Disease-Free Survival (DFS) and Overall Survival (OS) curves. Cox proportional hazard regression models established hazard ratios (HR), reported with a 95% confidence interval (CI). Results ILC exhibited distinctive characteristics compared to IDC, including older age, larger tumor size, higher estrogen receptor and progesterone receptor expression, and significantly lower HER-2 expression. The disease-free survival (DFS: ILC 86.6% vs. IDC 90.2%, P = 0.007) and overall survival (OS: ILC 90.5% vs. IDC 92.4%, P = 0.038) were worse for ILC than IDC. After applying Propensity Score Matching (PSM), the overall survival (OS: ILC 90.5% vs. IDC 93.2%, P = 0.046) was worse for ILC compared to IDC. Conclusion Patients diagnosed with Invasive Lobular Carcinoma (ILC) encounter distinct challenges, characterized by a lower survival rate, an elevated risk of metastasis when compared to those with Invasive Ductal Carcinoma (IDC). In order to gain a comprehensive understanding of ILC and to develop tailored, effective treatment strategies, it is imperative to investigate a variety of influencing factors in future research endeavors.